Dispatches from Blogistan : a travel guide for the modern blogger - Stefanac, Suzanne (Voices that matter., 2006)
The term "blog" wasn't coined until 1999 and yet by 2004, it had become Merriam-Webster's Word of the Year. Globally, the number of blogs is doubling every six months, with more than 50 million blogs online today. Here to offer a unique overview of the emerging phenomenon that even armchair observers will find curiosity-satisfying is Di spatches from Blogistan: A Travel Guide for the Modern Blogger. Filled with practical, easy-to-implement advice for making blogging more enjoyable, useful, and profitable, this book covers everything from blogging and how it fits into the history of journalism to practical tips for planning and managing a blog, attracting and retaining an active readership. Written by noted technology journalist and interactive media veteran Su zanne Stefanac, the book features a fresh and succinct approach; quotes and commentary from noted and celebrity bloggers (author/futurist Bruce Sterling, NPR commentator Farai Chideya, Craig Newmark of craigslist.com, and Cory Doctorow, Boing Boing editor and science fiction author, among others); an accompanying blog site (dispatchesfromblogistan.com); and more. Stefanac explores issues of trust, influence, privacy, discovery, and the power of collaborative discourse, making this is a blog book like no other!